2018
DOI: 10.1590/1806-9584-2018v26n346791
|View full text |Cite
|
Sign up to set email alerts
|

Vivências e perceções de sexualidade de portuguesas com mais de 65 anos

Abstract: Resumo: Este estudo objetiva compreender as vivências e perceções sexuais de mulheres portuguesas com mais de 65 anos. Foram realizadas entrevistas individuais semiestruturadas a 13 mulheres (sete casadas e seis viúvas), com idades compreendidas entre os 66 e os 85 anos, e a informação obtida foi analisada através do método da análise temática. Desta análise foram construídos 5 (cinco) temas - Perceções sobre papéis de género, Sexo “obrigação”, Sexualidade e envelhecimento, Medos do casamento e da sexualidade … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
1
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 25 publications
1
1
0
2
Order By: Relevance
“…In addition to domestic tasks, both seniors and young people attributed to women the work-family articulation ability. These results support the existing literature, as they show a double workload to fall on women, including the professional work and domestic work obligations (CITE, 2012;Queiroga et al, 2018).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In addition to domestic tasks, both seniors and young people attributed to women the work-family articulation ability. These results support the existing literature, as they show a double workload to fall on women, including the professional work and domestic work obligations (CITE, 2012;Queiroga et al, 2018).…”
Section: Discussionsupporting
confidence: 89%
“…When the focus was on the superiority and inferiority/submission dimensions, it was found that, in the environment, superiority was predominantly associated with men and inferiority/submission with women, which was reported mainly by young women. Other studies highlight women's disadvantaged position in society and within the couple, where a submission and yielding posture towards men is described: the man being considered a figure of authority and power (Fávero & Maracci, 2016;Fernandes, 2009;Queiroga et al, 2018). Fernandes (2009) argues that these postures are learned in the socialization process, which leads us to reflect on the generational transmission of gender ideologies, co-constructed in society.…”
Section: Discussionmentioning
confidence: 99%
“…Por conseguinte, os relatos das mulheres idosas nesse tempo de infância corroboram com o estudo realizado com mulheres portuguesas maiores de 65 anos, onde relataram a falta de comunicação com a família sobre a sexualidade, assim como, a propagação de mitos, preconceitos e o entendimento biológico dividido em relação aos modelos de gênero na submissão e omissão das mulheres. Dessa maneira, essa falta de diálogo gerou obstáculos nas relações afetivas e íntimas em outras fases da vida uma vez que, a educação que lhes eram oferecidas baseavam-se na dicotomia de gênero (Queiroga, Magalhães & Nogueira, 2018).…”
Section: Discussionunclassified
“…As mulheres idosas procuraram se dedicar aos filhos, família e as atividades domésticas, abdicando das suas necessidades e desejos sexuais. Nesse contexto, os tabus e o desconhecimento acerca da sexualidade decorrente da ausência de informações, colaboram para o desenvolvimento de desigualdades, sentimentos de medo, culpa, dúvidas, hesitações, vulnerabilidades e submissão (Nardelli et al, 2017;Queiroga, Magalhães & Nogueira, 2018).…”
Section: Discussionunclassified